ANALISIS TEORI SOSIAL KOGNITIF DALAM Q.S AN-NISA AYAT 69 DAN 140 - Abdurrohman Sholeh; Nur Hidayat; Yasin Baidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Humans are endowed with various abilities to develop themselves, one of which is cognitive ability that allows individuals to learn and solve problems. Along with the increasingly advanced era, the development of human cognition always experiences changes that become important discussions, especially regarding the factors that influence it. One factor that has a major influence on the development of cognition is the environment. This is in line with the Social Cognitive theory put forward by Albert Bandura, which shows a reciprocal relationship between personal cognition, social environment, and behavior. In addition, the Qur'an as the holy book of Muslims, contains teachings that are also relevant to the Social Cognitive theory, especially in terms of the relationship between humans and the environment and behavioral development. This study aims to interpret QS An-Nisa' verses 69 and 140 through a comparison of the interpretations of Al-Mishbah, Ibn Kathir's Interpretation, and Al-Munir's Interpretation, and to analyze its relevance to Albert Bandura's Social Cognitive theory. The results of the study indicate that the verses describe the importance of a positive environment and its impact on behavior, which is in line with the principles of Social Cognitive theory. This study is expected to provide a deeper understanding of how Islamic teachings, as reflected in the Qur'an, are in line with Social Cognitive theory in shaping good individual behavior and managing environmental influences